PRECIPITATION OF ABSENCE EPILEPSY IN THE COURSE OF ELECTRICAL STIMULATION OF PALEOCEREBELLAR CORTEX IN CATS WITH SIMPLE PARTIAL EPILEPSY MODEL - Godlevsky, L.S.; Stepanenko, K.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The effects of paleocerebellar cortex (nodulus, uvula) electrical stimulation (ES) (100-300 Hz, 0,25 ms, 150-250.A, duration of trial- 3-7 s, interstimuli intervals- 3,0-4,0 min) in artificially ventilated cats uponbenzilpenicillin- induced epileptic foci in sensorimotor cortex were investigated. ES caused a suppression of power of epileptic foci and this effect was not reproduced after electrocoagulation of cerebellar tissue neighboring the stimulative electrodes. Along with the suppressive effects upon the activity of the epilepticfoci, ES induced the formation of pronounced primarily positive component (PPC) of a spike discharge alongwith the induction of spike-wave discharges (SWD) (3/sec). Both phenomena were restricted to the zone ofpenicillin application. SWD activity substituted spikes and disappeared after renewal of epileptogen application. It was concluded that PPC and SWD are characteristic for the antiseizure effects of cerebellum on penicillin- induced foci in cats.